Computer·Managed Instructional Systems: An Essential Component of Educational Reform - David Bryant; Bettye MacPhail-Wilcox (Educational Considerations, 1986)
Computer managed instruction is a technological concept that links computers, other information processing technologies, the curriculum, and the teacher for more efficient and effective instructional management.